Scaffold hopping: Exploration of acetanilide-containing uracil analogues as potential NNRTIs. Issue 5 (1st March 2015) - Babkov, Denis A.; Valuev-Elliston, Vladimir T.; Paramonova, Maria P.; Ozerov, Alexander A.; Ivanov, Alexander V.; Chizhov, Alexander O.; Khandazhinskaya, Anastasia L.; Kochetkov, Sergey N.; Balzarini, Jan; Daelemans, Dirk; Pannecouque, Christophe; Seley-Radtke, Katherine L.; et al.
Graphical abstract: Abstract: In order to identify novel nonnucleoside inhibitors of HIV-1 reverse transcriptase two series of amide-containing uracil derivatives were designed as hybrids of two scaffolds of previously reported inhibitors. Subsequent biological evaluation confirmed acetamide uracil derivatives15a –k as selective micromolar NNRTIs with a first generation-like resistance profile. Molecular modeling of the most active compounds15c and15i was employed to provide insight on their inhibitory properties and direct future design efforts.